Gdy królewską godność zachowały tylko kamienne lwy…, czyli o językowej kreacji lwa w piosenkach Jacka Kaczmarskiego - Kępka, Izabela (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The main goal of the article is showing the language creation of a lion in songs by Jacek Kaczmarski. The theme of the lion, helps to show the situation of the people enslaved in a communist country. The lion, the symbol of power and bravery, in Kaczmarski’s poetry is mainly shown as an attraction in circus. It is weak, disoriented and frightened. This stereotypical proud animal, became a weak creature, which is laughed at by the spectators. Only fake lions made out of stone along with the Zodiac Leo and people named Lion, didn’t lose their proudness and bravery. Those can remind us about the characteristics of a true lion, but are also guardian of true, wise and honest authority. Kaczmarski’s lions symbolize an enslaved, weak nation that, on the other hand, have the awareness of their power and wait for the fall of the regime.